Gestantes vivendo com HIV/AIDS: Características antropométricas e peso ao nascer dos seus recém-nascidos - Bassichetto, Katia Cristina; Bergamaschi, Denise Pimentel; Bonelli, Iraci Cota; Abbade, Joelcio Francisco [UNESP] (FapUNIFESP (SciELO), 2013)
PURPOSE: To describe the anthropometric and pregnancy characteristics of women with HIV/AIDS, assisted by the Brazilian National Health System and the birth weight of their newborns. METHODS: The participants were women assisted at public STD/AIDS clinics of the Municipal Health system of São Paulo. The anthropometric characteristics were evaluated by trained nutritionists and other information was obtained from the medical records. For comparison of the survey data to those of the general population, secondary maternal and pregnancy data were obtained from live birth certificates through the Live Birth Information System. Continuous variables were summarized as mean and standard deviation or as the 25th, 50th and 75th percentiles and minimum and maximum values. The other variables are presented as percentages. Means were compared by the Student's t-test or Kruskal-Wallis test depending on the fulfillment of assumptions, with the decision based on the p value. RESULTS: We found the presence of inadequate maternal nutrition according to triceps skinfold (60.9%). The BMI/gestational age showed the presence of underweight (18.5%) and overweight or obesity (40%). There was no association between disease status (HIV or AIDS) and weight, height, and lean or fat mass. Mean newborn birth weight was lower than the value for the general population without infection or disease. The results of this study indicate the need to develop adapted curves to allow a more accurate nutritional assessment of this population group.
Anthropometric characteristics of HIV/AIDS: Pregnants and birth weight of theirs newborns
Keywords: Acquired immunodeficiency syndrome; Anthropometry; Birth weight; HIV; Pregnant women